WATER QUALITY MONITORING AND CONTROL SYSTEM IN FISH CULTIVATION POND USING ARDUINO CLOUD - Kusumawijaya, Wahyu; -, Syaifurrahman; Aula, Abqori (Faculty of Engineering, Universitas Tanjungpura, 2024)
Water quality is an important factor in supporting the life of living creatures, one of which is fish. Failure to maintain water quality can result in slower fish growth and can cause mass death. In the process of monitoring water quality, several environmental value are detected, namely water pH, water turbidity and water temperature. With the Internet of Things (IoT), monitoring water quality can be done using the Arduino Cloud application via a smartphone or computer anywhere in real time. These two parameters are given thresholds, the environmental water temperature threshold is between 28 - 30 °C and the water turbidity threshold is between 5 - 50 NTU. If one of the values exceeds the threshold, where the water temperature is higher than 30 °C or below 28 °C, the water turbidity is higher than 50 NTU or below 5 NTU, then a water change will occur as water quality control which starts with draining the water using a solenoid valve, then filling the water using a water pump. The measurement results showed that fish growth for 2 weeks was 17% with maintained water quality and the average percentage of error obtained in water temperature measurements was 0.314% and water turbidity was 2.769%.